PENERAPAN HUKUM ISLAM DI KERATON KASUNANAN SURAKARTA MASA PAKOE BOEWONO IV (TAHUN 1788-1820 M) - Katno, Katno (Profetika Jurnal Studi Islam, 2015)
Islamic law had been successfully applied in Indonesia as if about to be removed from the records. Just like the government policy in the Dutch colonialists who want to portray Snouck poor Islamic law at the time. Islamic law is law considered cruel and unjust towards women. Such an understanding is also happening in the Surakarta. Society considers the current Kasunanan still prevail is customary law. That's the background for the author to reveal in detail the history of Islamic law in Surakarta during PB IV.This esearch aims to determine the details of the implementation of Islamic law, determine the scope of application of Islamic law and to determine the factors that hinder the implementation of Islamic law in Surakarta during Pakubowono IV.The method used in this research is the analysis of qualitative Historical Method. The implementation of Islamic law in Surakarta during Pakubowono IV has been running well although there is a shortage due to several factors. The biggest factor that makes it less optimal implementation of Islamic law at the time it was because of the pressure and the Dutch intervention. The scope of application of Islamic law in Surakarta during Pakubowono IV covers almost all areas of Islamic law. Among these Islamic laws have been implemented to manage the political, criminal and civil.Factors that hinder the implementation of Islamic law in Surakarta during Pakubowono IV, among others: the Dutch intervention, lack of support and lack of indigenous political and military forces to support the establishment of Islamic law.